Hellburner : a novel of the Oregon files - Cussler, Clive; Maden, Mike (Cussler, Clive. Oregon files adventures., 2022)
"Juan Cabrillo and the crew of the Oregon must track down a nuclear torpedo before it unleashes World War III in this electrifying new installment of the #1 New York Times bestselling series."--